(untitled) (Journal of University of Babylon for Engineering Sciences, 2017)
Analytical formulations that is extremely important by understanding how can prepare the manufacturing process and the optimization of machining parameters such as cutting conditions, and tool geometries which is led to reduce the experimental tests needful. Finite element model belong numerical simulation method which is considered natural extension of analytical formulations as established a special relation to develop detailed of models during manufacturing process. It can provide detailed information from machining process that is depending on the cutting conditions such as cutting speed, chip formation, stress-strain analysis, and feed rate. The calibration procedure was carried out of finite element model and validation by comparing the experimental results and the corresponding numerical simulation data. The results indicate there is a good agreement between simulated values and experimental tests which depend to investigate on two types that is calibration and validation. This is because the validation of numerical simulation model and analytical formulations which is verified only when they have conform to experimental results. It concludes that the finite element model represents the real key to reduce the cost of manufacturing in terms of machining time saving and extend the duration of the cutting tool life.